RESIDUAL ACTIVITY OF BACILLUS THURINGIENSIS VAR. ISRAELENSIS AND BACILLUS SPHAERICUS AGAINST MOSQUITO LARVAE - N. Jahan; E. H. Jamali; M. F. Qamar (Journal of Animal and Plant Sciences, 2013)
Residual effect of Bacillus thuringiensis var. israelensis (Bti) Technical powder, WDG (water Dispersible Granules) and a Bacillus sphaericus (Bsph) was evaluated against laboratory-reared Anopheles stephensi and field collected Culex quinquefasciatus late third instars from Lahore, Pakistan. In general residual activity of both strains in seven different concentrations (100, 10, 1, 0.1, 0.01, 0.001 and 0.0001 ppm) for laboratory reared and in semi-field bioassays varied in both species of mosquito larvae. Bti TP residual activity varies from 51 days to 24 hours against laboratory reared A. stephensi larvae using maximum concentrations 100 ppm to minimum concentration 0.0001 ppm (fresh stock replacement every 24 hours). Whereas, Bsph TP indicated maximum residual effect for 18 days and minimum for 48 hours against the same species. Percent mortality was significantly higher (P=0.000) for A. stephensi against 100 ppm as compared to Bsph. However, the same effect (P=0.054) was observed for field collected Culex quinquefasciatus against 100 ppm Bsph. In conclusion field collected Culex quinquefasciatus larvae were more susceptible and have prolonged residual effect as compared to laboratory reared A. stephensi against Bsph while Bti have effect vice versa. Residual effect for field evaluation of Bti WDG under low treatment (0.2 mg/litre) against Culex quinquefasciatus lasted 14 days indicating more efficient for field bioassays as compared to laboratory.
Keywords: Anopheles stephensi; Residual activity; Bacillus thuringiensis; Bacillus sphaericus; Culex quinquefasciatus